Agreement Pattern on Entreupreunship-Based Partnership in Forest Management in West Java - Noor Rachman (International Journal of Latin Notary, 2021)
Forests as one of the national assets in the field of natural resources need serious attention, because forests play a very important role in the sustainability of the ecosystem in this open world. Forest management is a cross-gender, cross-generational and cross-sectoral responsibility. Given that forests are one of the determinants of ecosystems, their management must be improved in an integrated manner. Forest management is expected to greatly help income and foreign exchange earnings for the state in order to achieve people's prosperity through the entrepreneurship pattern. However, the increased exploitation of forest resources without preserving them will accelerate the destruction and survival of the forest. This means that it is possible to hinder the improvement of the welfare of the surrounding community . So a balance is needed between exploitation and management.